On Local Government Spending and Taxation Behaviour - Effect of population size and economic condition - Antti Moisio (European Regional Science Association (ERSA), 2001)
This paper examines the Granger-causality between total expenditures, own source revenues, grants received from state and long term loans for 12 subgroups of Finnish municipalities. Two panel data sets that cover the years 1985-1992 and 1993-1999 are used in order to compare the effect of change from matching grants to formula based grants system. The main findings are that the grant system reform has resulted in more careful economic decision-making among the municipalities. For instance, the largest municipalities that used to have “spend and tax” causality now have “simultaneous” causality between expenditures and revenues. Another finding is that the smallest municipalities seem to be careful in their budgetary process irrespective of the grant system. The implications of the results are that the reaction to specific central state measures may differ considerably between separate groups of municipalities. The differences should be taken into account before making any important changes or restrictions that affect municipalities' budgetary variables.
Keywords: 330